20. DIABETES IN RAMADHAN’ EDUCATION PROGRAM: MAXIMIZING BENEFITS, MINIMIZING RISKS - Mohamed Shah, Fatimah Zaherah; Eddy Warman, Nur ‘Aini; Awang, Mohd Hazriq; Mohamed, Aimi Fadilah; Zainordin, Nur Aisyah; Abdul Ghani, Rohana Abdul (Journal of Islamic, Social, Economics and Development, 2024)
The incidence of Type2 Diabetes Mellitus (DM) in Malaysia is increasing, with 59% in Malays followed by other races. Fasting in Ramadhan is beneficial, however in those with DM, it is challenging, requiring sufficient and comprehensive medical advice. This novel diabetes in Ramadhan dietary education program aims to facilitate knowledge attainment to mitigate the risk of complications in Ramadhan and to pave the way to fasting safely. This activity was conducted at the UiTM Medical clinic facilities by the Endocrine team consisting of physicians and diabetic educator, facilitated by a specially designed educational guide, which was a compilation of important information on managing the challenges DM patients during fasting, concentrating on healthy dietary practices - gathered from the Malaysian DM clinical practice guidelines and the International Diabetes Federation (IDF) Diabetes in Ramadan guideline. This compendium was designed mainly in the Malay language to enable better understanding in Malaysian population. The program provided comprehensive education on fasting in Ramadhan for people with DM in an engaging manner, organised into two main parts: (1) small group educational-lectures; and (2) personalised risk stratification with medical advice. The educational reference guide detailed important information on the risk categories for fasting in Ramadhan, timing of blood sugar monitoring, when to break the fast in the event of complication with management steps, medication adjustment, and dietary advice with practical tips. This innovative program has been tailored for use in the local population, and provides an essential service that is hugely beneficial, but currently lacking in this country. With this comprehensive and engaging platform, important information on managing diabetes in Ramadhan can be accessible to a wider population, leading to better patient care, and hence a has huge potential for sustainability. A larger multi-centre program will be required for a greater impact.